Pediatric COVID-19 risk factors in Southeast Asia-Singapore and Malaysia: a test-negative case–control study - Wong, Judith Ju Ming (2022)
There is a scarcity of population-level data of pediatric COVID-19 infection from Southeast Asia. This study aims to describe and compare epidemiological, clinical, laboratory and outcome data among pediatric COVID-19 cases versus controls in two neighboring countries, Singapore and Malaysia. We used a test-negative case-control study design recruiting all suspected COVID-19 cases (defined by either clinical or epidemiological criteria) from January 2020 to March 2021 admitted to two main pediatric centers in Singapore and Malaysia. Data were collected using a standardized registry (Pediatric Acute and Critical Care COVID-19 Registry of Asia). The primary outcome was laboratory-confirmed COVID-19. Univariate and multivariable logistic regression analysis was used to determine factors associated with COVID-19. This study included 923 children with median age of 4 (interquartile range 2-9) years. Of these, 35.3% were COVID-19 cases. Children with COVID-19 were more likely to be asymptomatic compared with controls (49.4 versus 18.6%; P < 0.0001). They were also less likely to develop respiratory complications, such as bronchitis or pneumonia, or organ dysfunction. Four (1.2%) of our COVID-19 patients required respiratory support compared with 14.2% of controls needing respiratory support. COVID-19 cases tended to have lower neutrophil count but higher hemoglobin compared with controls. There were no reported deaths of COVID-19 infection; in contrast, 0.7% of the control group died. In the multivariable analysis, older age, travel history, and close contact with an infected household member were associated with COVID-19 infection. This study shows that the majority of pediatric COVID-19 cases were of lesser severity compared with other community acquired respiratory infections.